インフラサウンド解析ソフトウェアの開発 - 小松, 孝康; 山本, 真行; 石原, 吉明; 金尾, 政紀; 阿部, 琢美; Takayasu, Komatsu; Masa-yuki, Yamamoto; Yoshiaki, Ishihara; Masaki, Kanao; Takumi, Abe (2010)
第33回極域気水圏シンポジウム 11月30日（火） 国立極地研究所 ２階大会議室 conference object